Potensi Gastronomi Halal di Pecinan Chinatown Bandung Utara - Fannisa Rahayu Saraswati; Naifa Ananda Putri; Asep Parantika (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is a type of descriptive qualitative research. The data collected in this study are: (1) Selected restaurant data is done by searching from bloggers and social media when people eat at Chinatown Chinatown, which are the choices, (2) Restaurants obtained from point 1, discussed with the group, which areas are restaurants that are considered halal. This research is a type of descriptive qualitative research. There are approximately 70 percent of stalls or stands selling various foods and 30 percent of them selling Chinese food at various prices that can be enjoyed in Chinatown. However, several food and retail tenants that fill the Chinatown Chinatown area still have nonhalal food for non-Muslims, to maintain legendary culinary offerings.CLIL, ESP, oral communication skills, written communication skills